Rede de Urgência e Emergência: um estudo de caso na Região Coração do Estado de São Paulo - Pereira, Ana Paula Fernandes (2017)
This study will analyze changes in the implantation of Urgency and Emergency Netwok (RUE) health system in the region of Coração, state of São Paulo, as well as RUE challenges and achievements in this location based on guidelines described in official documentation which organize the implantation of RUE. This investigation was composed of a descriptive and exploratory case study that is based on qualitative research concepts to identify elements for analysis of the implantation, and it was performed in two stages: theoretical analysis and semi-structured interview. The method Analysis of Contents was utilized for data analysis of interviews. Based on information from documents and data analysis of interviews the material was organized in categories and defined in five themes: (1) History of RUE in the region of Coração; (2) Relations between National Department of Health, Regional Department of Health (DRS) and Municipalities in the construction of RUE; (3) Variables contributing to the implantation of RUE, and (4) Co-management as a device contributing to the consolidation of RUE, and (5) Resistance at change in the organization hamper at the process in implantation gives RUE. This study allowed to realize that National Department of Health’s activity is acknowledged both as encouraging and troublesome for the implantation of RUE. Obstacles in the proposition of a health project which could overcome party-political relations and local interests. Sub-funds are a challenge for the realization of RUE especially in small municipalities, and it makes the implantation of local and regional Emergency Mobile Support Service (SAMU) difficult. The study enlists some elements promoting RUE, such as the relevance of scheduled meetings between representative parties of RUE devices and municipalities of the region, the creation of a regulative forum for assessment of distribution and flow of patients, and management resources contributing to the organization of care support inside the “Hospital Entry Doors”. Therefore, this study has showed that financial investments are required in order to implant RUE in this location – one of the difficulties highlighted by municipalities involved – and that a project towards consolidation of Global Care System (SUS) and patient care must be prioritized in relation with local party-political projects